1980
DOI: 10.1038/bjc.1980.224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclosporin A on the growth and spontaneous metastasis of syngeneic animal tumours

Abstract: Summary.-Cyclosporin A (Cy A), a novel immunosuppressive agent with apparently selective inhibitory effects on T lymphocytes and little myelotoxicity, was tested for its effects on a variety of syngeneic animal tumours including sarcomas, carcinomas and a T-cell lymphoma. Cy A, given orally or parenterally in repeated doses, had no effect on the growth rates of any of the tumours tested, but a highly significant effect on metastasis was seen in many cases. All the sarcomas examined in both rats and mice, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 11 publications
7
19
0
Order By: Relevance
“…Using this assay, the only obvious effect of CyA was a reduction in the number of FcR+ cells infiltrating the tumour. Similar observations have been made by Eccles et al (1980), who used both mouse and rat fibrosarcomas.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Using this assay, the only obvious effect of CyA was a reduction in the number of FcR+ cells infiltrating the tumour. Similar observations have been made by Eccles et al (1980), who used both mouse and rat fibrosarcomas.…”
Section: Discussionsupporting
confidence: 84%
“…Recent reports have now established that the influence of CyA on the immune system is much more extensive (Kunkel & Klaus, 1980;Klaus, 1981). Our data showed that at (Eccles et al, 1980). Using this assay, the only obvious effect of CyA was a reduction in the number of FcR+ cells infiltrating the tumour.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…With oestrogen-dependent tumours, dormancy extending for very long periods can be detected by transplanting the tumours into noirmal recipients, in which no growth occurs, and then admininistering oestrogen, when macroscopic growth sets in. Noble & Hoover (1975), Eccles & Alexander (1975) and Eccles et al (1980) found that dormant metastases were common in chemically induced rodent sarcomas and lymphomas which did not metastasize frequently when transplanted to normal syngeneic animals, in which they can be "cured" by surgical removal of the primary implant and its draining node. When such tumours were allowed to grow for a set period before being excised surgically, dormant metastases, seeded from the primary implant before it was excised, were revealed as lung or distant lymph-node metastases after immunosuppression, especially that caused by Cyclosporin A (Eccles et al, 1980), long after surgery (Fig.…”
Section: Dormant Mnetastasismentioning
confidence: 99%
“…In rodent tumour studies IL-2 Ley et al, 1991), (Golumbek et al, 1991) and y-IFN (Watanabe et al, 1989;)-secreting tumour cells have each been shown to induce protection against parental tumour cell challenge. In order to determine which of these therapeutic routes might be the more feasible, we have compared the properties of IL-2 and IL-4-secreting tumour cells in a single murine tumour, the transplantable fibrosarcoma, FS29 (Eccles et al, 1980). We have demonstrated that either IL-2, or IL-4-secreting cells show a poor ability to induce the rejection of admixed parental cells.…”
mentioning
confidence: 99%